THE RELATIONSHIP BETWEEN LEARNING MOTIVATION, PARENTS’ ATTENTION, AND PEERS INTERACTION WITH STUDENTS MATHEMATICS LEARNING OUTCOMES OF CLASS VIII SMP NEGERI 13 YOGYAKARTA - Efika Lestari; Suparyan Suparyan (Universitas Ahmad Dahlan, 2017)
The low of students’ mathematics learning outcome associated with many factors. Students’ low motivation, parents’ attention, peer interaction are several factors that were to have a relation with the mathematics learning outcomes. Therefore, this study aimed to determine whether there is a positive and significant relationship between learning motivation, parents’ attention and peer interaction with student mathematics learning outcomes of class VIII SMP Negeri 13 Yogyakarta on the odd semester in the academic year of 2016/2017. The population in this study was all eight grade students in SMP Negeri 13 Yogyakarta on the odd semester in the academic year of 2016/2017 consisting of 133 students in four classes. The sample was class VIII B consisting of 33 students. The random sampling technique was used in taking the sample. Data were collected by questionnaires and tests. The questionnaire was used to find out the students’ learning motivation, parents’ attention, and peer interaction, while the test was used to find out the students’ learning outcomes. The research instrument: validity test, different power test, and reliability test. The requirement analysis includes a test of normality, test of linearity, and the test independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The finding shows a positive and significant relationship between motivation, parents’ attention and peer interaction toward mathematics learning outcomes with is with = 0,6764 and = 0,4576 with with SR = 35,5937%, SR and SR , SE , SE = 6,8961% and SE = 11,8651%.